Is "Benign Childhood Epilepsy with Centrotemporal Spikes” Always Benign? - SAEED, Muhammad; AZAM, Muhammad; SHABBIR, Nadeem; QAMAR, Shair Ali (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Saeed M, Azam M, Shabbir N, Qamar ShA. Is "Benign Childhood Epilepsy with Centrotemporal Spikes" Always Benign? Iran J Child Neurol. 2014 Summer;8(3): 39-45. Abstract Objective To determine the prevalence of associated behavioral problems and prognosis with Benign Childhood Epilepsy with CentroTemporal Spikes (BCECTS). Descriptive, Cross Sectional study that was conducted from October 2009 to April 2013 in the Department of Pediatric Neurology, the Children’s Hospital Taif, KSA. Material & Methods This study was conducted after approval from the Ethics Committee of the Children’s Hospital Taif, Saudi Arabia. Thirty-two patients from the age of 3 to 10 years old were recruited from the pediatric neurology clinic over a period of 4 years. All the patients were selected based on history, EEGs, and neuropsychological and neurological examinations. EEGs were performed for all the patients while in awake and sleep states. Those who had centrotemporal discharges were included in the study. All the patients also underwent a brain MRI. Only two patients had mild cortical atrophy but developmentally they were normal. Results In our study, prevalence of BRE is 32/430 (7.44%). Among the 32 cases, 24 were male and eight were female. Six cases out of 32 indicated a family history of BRE. Twenty-eight cases had unilateral right sided centrotemporal discharges and four had bilateral discharges. Conclusion It is possible that for BECTS, a high number of seizures might play an important role in the development of mild cognitive impairment and/or behavior disturbances. References Bradley WG, Daroff RB, Fenichel JM, Jahrovic J. Neurology of clinical practice. 5th Ed. 2009: pp. 1953-1990. Berg AT, Berkovic SF, Brodie MJ, Buchhalter J, Cross H, Van Emde Boas M, et al: Revised terminology and concepts for organization of seizures and epilepsies: Report of the ILAE Commission on Classification and Terminology, 2005–2009. Epilepsia. 2010; 51(4):676-685. Weglage J, Demsky A, Pietsch M. Neuropsychological, intellectual, and behavioral findings in patients with centrotemporal spikes with and without seizures. Dev Med Child Neurol. 1997; 39:646. Kramer U. Atypical presentations of benign childhood epilepsy with centrotemporal spikes: a review. 2008. J. Child Neurol 23 (7): 785–90. Chahine LM, Mikati MA. Benign pediatric localizationrelated epilepsies. Epileptic Disord. 2006. 8(4): 243–58. Danielsson J, Petermann F. Cognitive deficits in children with benign rolandic epilepsy of childhood or rolandic discharges: a study of children between 4 and 7 years of age with and without seizures compared with healthy controls. Epilepsy Behav. 2009; 16:646–651. Ay Y, Gokben S, Serdaroglu G, Polat M, Tosun A, Tekgul H, et al. Neuropsychologic impairment in children with rolandic epilepsy. Pediatr Neurol. 2009; 41:359–363. Wirrell E, Sherman EM, Vanmastrigt R, Hamiwka L. Deterioration in cognitive function in children with benign epilepsy of childhood with central temporal spikes treated with sulthiame. J Child Neurol. 2008; 23:14–21. Lundberg S, Eeg-Olofsson O. Rolandic epilepsy: a challenge in terminology and classification, European Journal of Paediatric Neurology. 2003; 7: 239–241. Bouma PA, Bovenkerk AC, Westendorp RG, Brouwer OF. The course of benign partial epilepsy of childhood with centrotemporal spikes: a meta-analysis. Neurology. 1997;48:430-437. Deltour L, Quaglino V, Barathon M, De Broca A, Berquin P. Clinical evaluation of attentional processes in children with benign childhood epilepsy with centrotemporal spikes (BCECTS) Epileptic Disord. 2007; 9:424–431. Nicolai J, Aldenkamp AP, Arends J, Weber JW, Vles JS. Cognitive and behavioral effects of nocturnal epileptiform discharges in children with benign childhood epilepsy with centrotemporal spikes. Epilepsy Behav. 2006; 8:56–70. Goldberg-Stern H, Gonen OM, Sadeh M, Kivity S, Shuper A, Inbar D. Neuropsychological aspects of benign childhood epilepsy with centrotemporal spikes. Seizure. 2010; 19:12–16. Genizi J, Shamay-Tsoory SG, Shahar E, Yaniv S, Aharon- Perez J. Impaired social behavior in children with benign childhood epilepsy with centrotemporal spikes. J Child Neurol. 2012; 27:156–161. Zenkov LR, Konstantinov PA, Shiriaeva IIu, Miasnikov VN, Sirazitdinova EB, Shevel’chisnkiĭ SI. Mental and behavioral disorders in idiopathic focal epileptiform spikes. Zh Nevrol Psikhiatr Im S Korsakova. 2007; 107:39–49. Winckler MIB, Rotta NT. Prognostic factors for recurrence of a first seizure during childhood. Arq Neuropsiquiatr.1997; 55:749-756. Holmes GL. Rolandic epilepsy: clinical and electroencephalographic features. In: Degen R, Dreifuss FE, editors. Benign localized and generalized epilepsies of early childhood. Amsterdam: Elsevier ;1992: p.29-43. Gregory DL, Wong PKH. Clinical relevance of a dipole field in rolandic spikes. Epilepsia. 1992; 33:36-44. Bouma PAD, Bovenkerk AC, Westendorp RGJ, Brouwer OF. The course of benign partial epilepsy of childhood with centrotemporal spikes: a meta- analysis. Neurology. 1997; 48: 430-437. Fejerman N, Caraballo R, Tenembaum S. Atypical evolutions of benign -localization-related epilepsies in children: are they predictable? Epilepsia. 2000; 4: 380-390. Peters JM, Camfield CS, Camfield PR. Population study of benign rolandic epilepsy: is treatment needed? Neurology. 2001; 57: 537-539. Holmes GL. Rolandic epilepsy: clinical and electroencephalographic features. In Degen R, Dreifuss FE. editors. Benign localized and generalized epilepsies of early childhood. Amsterdam: Elsevier 1992:p. 29-43. Laub MC, Funke R, Kirsch CM, Oberst U. BECT: comparison of cerebral blood flow imaging, neuropsychological testing and long-term EEG findings. Epilepsy Res Suppl. 1992;6:95-98. Coppola G. Cognitive and linguistic abnormalities in benign childhood epilepsy with centrotemporal spikes. Acta Paediatr. 2011;100(5):768-772. Sarco DP, Boyer K, Lundy-Krigbaum SM, Takeoka M, Jensen F, Gregas M, Waber DP. Benign rolandic epileptiform discharges are associated with mood and behavior problems. Epilepsy Behav. 2011;22 (2):298-303. Jones JE, Watson R, Sheth R, Caplan R, Koehn M, Seidenberg M, et al. Psychiatric comorbidity in children with new onset epilepsy. Dev Med Child Neurol. 2007;49:493-7. Austin JK, Harezlak J, Dunn DW, Huster GA, Rose DF, Ambrosius WT. Behavior problems in children before first recognized seizures. Pediatrics. 2001; 107:115-22. Bhise VV, Burack GD, Mandelbaum DE. Baseline cognition, behavior, and motor skills in children with new-onset, idiopathic epilepsy. Dev Med Child Neurol. 2010;52:22-6. Kavros PM, Clarke T, Strug LJ, Halperin JM, Dorta NJ, Pal DK. Attention impairment in rolandic epilepsy: systematic review. Epilepsia. 2008; 49:1570-80. Beaussart M. Benign epilepsy of children with Rolandic (centro-temporal) paroxysmal foci: A clinical entity: Study of 221 cases. 1972. Epilepsia 13 (6): 795–811.